The development of high-growth agribusinesses in the aftermath of the 2008 financial crisis. (20th September 2019) - Arimany-Serrat, Nuria; Tarrats-Pons, Elisenda; Nylund, Petra
The impact of the 2008 financial crisis has led the region of Central Catalonia, Spain, to rely even more on agribusiness. This industry represents a large share of employment and sales income in the region. In addition, high-growth firms drive a disproportionate share of regional economic growth. We therefore analyse the economic and financial health of high-growth agribusinesses in Central Catalonia during the period 2008-2013. We find that these firms exercise frugal financial management during the studied years, and that their economic profitability is a function of their solvency and the employee productivity. We conclude by discussing the implications of these findings.